(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Plants have played a major role in the production of biological compounds for the formation of drugs. Their role may either become a base for the development of medicine, a natural blue print for the development of new drugs or a phytomedicine to be used for the treatment of diseases. Acharya Charaka has quoted that none of the plants found around us are non-medicinal. Clitoria ternatea commonly known as Aparajita or Butterfly pea is a medicinal plant belonging to the family Fabaceae. In various Ayurvedic classics and Ayurvedic material medica, this plant is reported to be used in insect bites, skin diseases, asthma, burning sensation, inflammation, leucoderma, leprosy and pulmonary tuberculosis. A good number of anti-inflammatory drugs are available in modern medicine, among them some are expensive and some are having adverse effects in long term uses. Thus a need arises to find a safer and efficient drug from the natural resources, which will be simple, effective and not having any adverse effect. In the present study, preliminary phytochemical study and anti-inflammatory study of Kashayam (decoction) of root of Aparajita were carried out to confirm the presence of various phytochemical substances and to determine the anti-inflammatory action against diclofenac sodium in carrageenan induced rat paw edema model. The results of experimental study showed significant anti-inflammatory action of Kashayam (decoction) of Aparajita roots in acute inflammation compared to control and near to the action of diclofenac sodium, which suggests that Aparajita is potential natural anti-inflammatory drug.